2012
DOI: 10.1074/jbc.m112.419127
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides Differentially Regulate Protrudin Localization through the FYVE Domain

Abstract: Background: Regulation of FYVE domain proteins by phosphoinositides other than PtdIns(3)P is not known. Results: PtdIns(4,5)P 2 , PtdIns(3,4)P 2 , and PtdIns(3,4,5)P 3 bind the FYVE domain of protrudin. Conclusion: PtdIns(4,5)P 2 , PtdIns(3,4)P 2 , and PtdIns(3,4,5)P 3 differentially regulate cellular protrudin function. Significance: This study provides new insight into how phosphoinositides modulate neurite formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 52 publications
2
39
2
Order By: Relevance
“…However, Saita et al (16) identified an interaction of protrudin with the ER-localized VAP-A, and Gil et al (17) localized some protrudin at ER, which increased dramatically upon deletion of the FYVE domain. Matsuzaki et al (25) used mass spectrometry to identify proteins interacting with protrudin, and a number were ER proteins, as well as the KIF5 molecular motor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Saita et al (16) identified an interaction of protrudin with the ER-localized VAP-A, and Gil et al (17) localized some protrudin at ER, which increased dramatically upon deletion of the FYVE domain. Matsuzaki et al (25) used mass spectrometry to identify proteins interacting with protrudin, and a number were ER proteins, as well as the KIF5 molecular motor.…”
Section: Discussionmentioning
confidence: 99%
“…The FYVE domain is of particular interest because it mediates interactions with the plasma membrane (17), which might play a role in ER-network formation. We generated a mutant lacking the FYVE domain, and whereas protrusions were induced by overexpression of wild-type HA-protrudin, as described previously (13), expression of HA-tagged ΔFYVE protrudin did not induce these (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has recently been shown for the neuronal protein protrudin, that its FYVE domain binds to other phospholipids including PI(4,5)P2 (Gil et al, 2012). It is possible that newly synthesized MOBP could also associate with PI(4,5)P2-containing lipid rafts.…”
Section: Fyn-mediated Translation Of Mobp Mrnamentioning
confidence: 99%
“…These domains are highly homologous, and most FYVE domains specifically bind PI(3)P (Lemmon 2008; Kutateladze 2007; Kutateladze 2010)), although recently the FYVE domain of protrudin was shown to bind PI(4,5)P 2 , PI(3,4)P 2 , and PI(3,4,5,)P 3 (Gil et al 2012). Three motifs found in FYVE domains (WxxD, RR/KHHCR, and RVC) shape a cationic patch that interacts with PI(3)P. PI(3)P plays a key role in membrane trafficking and is found in specific subcellular locales, including the cytoplasmic face of early endosomes, multivesicular bodies, and phagosomes (Burd and Emr 1998; Gaullier et al 1998; Patki V et al 1998).…”
Section: Phosphoinositide Binding Modulesmentioning
confidence: 99%